SISTEM DRAINASE ALIRAN BAWAH TANAH UNTUK DAERAH RAWAN LONGSOR (STUDI KASUS SUB DAS SUNGAI CIKAPUNDUNG, BANDUNG) - Redaksi Tim Jurnal (FORUM MEKANIKA, 2017)
Cikapundung River Restoration lies in a river border with a steep sloping slope and waves to the west - east which is formed from the flow of the river cikapundung. Generally, the soil structure of the Cikapundung River Basin slope is residual ground, corrosion stone and colluvial deposition,which caused vulnerable to landslides. It was also separate and able to keep water. Therefore, shear strength is weak, especially if water is saturated. In this case landslides always occur when it rains. In general, this is due to high rainfall with a certain duration, thus causing the stability of the slope is disrupted. Another cause is the non-functioning drainage system because it is covered by some material from the slopes submitted by water. Therefore, the water rubs the slope.